2016
DOI: 10.1159/000443622
|View full text |Cite
|
Sign up to set email alerts
|

Cotton Wool Spots after Anti-Vascular Endothelial Growth Factor Therapy for Macular Edema Associated with Central Retinal Vein Occlusion

Abstract: Purpose: To report a case series, whereby we encountered a transient increase in retinal cotton wool spots (CWS) following anti-vascular endothelial growth factor (anti-VEGF) therapy for the treatment of macular edema secondary to central retinal vein occlusion (CRVO). Methods: Eighteen eyes were treated with intravitreal aflibercept (IVA), and 5 were treated with intravitreal ranibizumab (IVR). Fundus photographs obtained 1 month after initial IVA or IVR injections were retrospectively evaluated for the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 32 publications
(41 reference statements)
1
4
0
Order By: Relevance
“…Campochiaro et al found the mean time from diagnosis of BRVO to screening was 3.5 months with duration ≤3 months in 65% of patients. 8 In our study 76.2% cases presented within 6 months of onset of symptoms. Mean study eye baseline BCVA was 6/18 and mean baseline CMT was 520.5 µ in a study by Campochiaroet al [9].…”
Section: Original Research Articlesupporting
confidence: 47%
“…Campochiaro et al found the mean time from diagnosis of BRVO to screening was 3.5 months with duration ≤3 months in 65% of patients. 8 In our study 76.2% cases presented within 6 months of onset of symptoms. Mean study eye baseline BCVA was 6/18 and mean baseline CMT was 520.5 µ in a study by Campochiaroet al [9].…”
Section: Original Research Articlesupporting
confidence: 47%
“…After these phase III studies, 9 initial monthly injections of ranibizumab were performed in the RAVE trial [16] and 7 initial monthly injections in the SHORE study [17] . Multiple intravitreal injections of anti-VEGF agents can increase the risk of systemic or ocular complications and may be associated with economic burden despite favorable treatment outcomes [18] . Further, it remains unclear whether such large numbers of injections are necessary for the initial treatment of ME after CRVO.…”
Section: Introductionmentioning
confidence: 99%
“…However, there were no FA images in this publication. A retrospective study estimated that 22.8% of eyes with central retinal vein occlusion (CRVO) developed cottonwool spots after an initial aflibercept injection and indicated that cotton-wool spots were reversible once the circulatory disturbance of the capillary bed was resolved (23).…”
Section: Discussionmentioning
confidence: 99%